2017
DOI: 10.1038/s41467-017-00808-w
|View full text |Cite|
|
Sign up to set email alerts
|

The chromosomal organization of horizontal gene transfer in bacteria

Abstract: Bacterial adaptation is accelerated by the acquisition of novel traits through horizontal gene transfer, but the integration of these genes affects genome organization. We found that transferred genes are concentrated in only ~1% of the chromosomal regions (hotspots) in 80 bacterial species. This concentration increases with genome size and with the rate of transfer. Hotspots diversify by rapid gene turnover; their chromosomal distribution depends on local contexts (neighboring core genes), and content in mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
155
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(177 citation statements)
references
References 73 publications
11
155
0
1
Order By: Relevance
“…To partition this graph, we established a statistical model taking into consideration that persistent genes share conserved genomic organizations along genomes [27] and that horizontally transferred genes (i.e. shell and cloud genes) tend to insert preferentially in a few chromosomal regions (hotspots) [28]. Thereby, PPanGGOLiN assumes that two gene families that are consistent neighbors in the graph are more likely to belong to the same partition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To partition this graph, we established a statistical model taking into consideration that persistent genes share conserved genomic organizations along genomes [27] and that horizontally transferred genes (i.e. shell and cloud genes) tend to insert preferentially in a few chromosomal regions (hotspots) [28]. Thereby, PPanGGOLiN assumes that two gene families that are consistent neighbors in the graph are more likely to belong to the same partition.…”
Section: Resultsmentioning
confidence: 99%
“…the average number of adjacent edges between gene families of the same partition, is 2.80 for the persistent genome while the shell genome has a higher average degree (3.95, P=5.0e-6 with bilateral unpaired 2-sample Student's t test) and the cloud a lower one (1.97, P=3.3e-40 with the same test). The shell genome is the most diversified in terms of network topology with many interconnections between families reflecting a mosaic composition of regions from different HGT events [28]. The major part of the cloud has a shell-like graph topology with a large connected component containing 60% of the nodes.…”
Section: Illustration Of a Partitioned Pangenome Graph Depicting The mentioning
confidence: 99%
“…Proteobacteria T4‐like phages are also targets of external mobile DNA (Edgell et al ., ), so phages from diverse bacterial hosts may facilitate the integration of other mobile element classes (Foley et al ., ). Furthermore, in general horizontally transferred genes in bacterial genomes, including Firmicutes, are preferentially located in hotspot regions, often with mobile elements (Oliveira et al ., ). Since aci1 appears to reside in an integration hotspot in the genome, it is still at risk of further mobilization.…”
Section: Discussionmentioning
confidence: 97%
“…4, information on the assembly scaffolds is in Supporting Information Table S4, and alignment statistics for the three strains with prophages are in Supporting Information Table S5. 2000). Furthermore, in general horizontally transferred genes in bacterial genomes, including Firmicutes, are preferentially located in hotspot regions, often with mobile elements (Oliveira et al, 2017). Since aci1 appears to reside in an integration hotspot in the genome, it is still at risk of further mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…These bacterial genomes replicate bidirectionally and the regions near the origin generally have highly transcribed genes due to gene dosage effects. As prophages are transcriptionally mostly silent and should not interfere with the expression of bacterial household genes, it was postulated that prophages should preferentially be inserted away from the origin of replication (Canchaya et al ., ; Bobay et al ., ; Oliveira et al ., ). Indeed, dividing up Negativicute genomes into 20 equally sized windows, with each window representing 5% of the chromosome length, we found that Negativicute prophages were not distributed randomly across bacterial genomes ( P < 0.01, χ 2 test), with a trend towards insertion towards the terminus of replication (Fig.…”
Section: Resultsmentioning
confidence: 99%